REPRESENTASI NILAI FILIAL PIETY (孝, XIÀO) DALAM KESANTUNAN BERBAHASA PADA FILM HOW TO MAKE MILLIONS BEFORE GRANDMA DIES - Yona Fitri Amri; Elyana; Alrizni Nadia Febritianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the representation of filial piety (孝, xiào) values in language politeness strategies in the film How to Make Millions Before Grandma Dies. The study is motivated by the importance of understanding how language use in film media represents cultural values, particularly respect, care, and responsibility toward parents within family relationships. This research employed a qualitative method with a descriptive approach, using dialogues among characters containing language politeness strategies and filial piety values as the data source. Data were collected through observation and note-taking techniques, while data analysis applied Brown and Levinson’s (1987) politeness strategy theory. The findings reveal that all politeness strategies proposed by Brown and Levinson are represented in the film, namely positive politeness, negative politeness, bald on record, and off record. Positive politeness emerges as the most dominant strategy, reflecting attention, respect, and emotional closeness within family relationships. Negative politeness demonstrates concern for parents’ emotional well-being, bald on record is used to express responsibility firmly, while off record indicates that the practice of filial piety may also be influenced by personal interests and economic factors. The study identifies three main forms of filial piety values, namely respect, affection, and responsibility toward parents, indicating that language politeness functions as a representation of cultural values in modern family life.